Inventory Control at The Perintis Cimaung Pharmacy Using Open Source Enterprise Resource Planning System: Odoo 14.0 - Krisnawanti Krisnawanti; Nava Gia Ginasta; Muhammad Faisal Nasrudin; Amida Anis Nasution (Institut Pendidikan Indonesia, 2023)
Along with the times and technology, more and more companies are switching from manual management of business processes to integrated information systems. Perintis Pharmacy is a pharmacy located in the Bandung district. Perintis Pharmacy has been serving its customers since 2010. However, Perintis Pharmacy has experienced several problems, where all business processes are still carried out manually. Errors frequently occur in both the service process and the inventory management system. Errors in stock calculations and ordering are the main obstacles. This causes the Pharmacy to experience losses both in terms of service quality and financially. So it is necessary to implement an integrated system so that inventory management becomes more effective and efficient, namely the application of an Enterprise Resource Planning (ERP) system that is integrated with forecasting simulations to obtain a more accurate amount of drug procurement. Demand forecasting is done using Time Series data with the Single Exponential Smoothing method, given the fluctuating demand every month. Then the forecasting results are integrated with the ERP system using the Odoo 14.0 application in the invoice, purchase, and inventory modules. By using the Odoo 14.0 application, it is expected that Perintis Pharmacy can increase efficiency and effectiveness in managing drug supplies so as to improve service quality and financial benefits.